مظاهر عصرنة المرفق العام في الجزائر - بن حميدة, سليمة (University of Eloued جامعة الوادي, 2022)
تسعى الدولة الج ا زئرية الى الحرص عمى إشباع الحاجات العامة للأف ا رد مف خلاؿ النشاط المرفؽ العا الذي تتنوع أقسامو عمى حسب الزوايا التي ينظر إلييا منيا، وكؿ ىذه الم ا رفؽ تقو عمى تحقيؽ المصمحة العامة للأف ا رد. كما أولت الج ا زئر اىتمامات بالغة الأىمية لأجؿ تحسيف الخدمة بالم ا رفؽ العمومية والسعي لعصرنتيا وىذا مف خلاؿ الاستجابة لتطمعات المواطف ومقتضيات التطور والحداثة وىو الأمر الذي يجعؿ مف كافة السياسات مف تجسيد ذلؾ عمى مستوى الم ا رفؽ العامة وذلؾ باستعماؿ التكنولوجيا الحديثة والمتمثمة في الإدارة الإلكترونية وىو ما يتعمؽ باستحداث المرصد الوطني لممرفؽ العا وتطويره عمى جميع المستويات الداخمية والخارجية خدمة لممصالح العامة ..The Algerian state seeks to ensure that the general needs of individuals are satisfied through the activity of the public facility, whose sections vary according to the angles from which it is viewed, and all these facilities are based on achieving the public interest of individuals. Algeria has also given very important concerns to improve the service in public utilities and strive to modernize it by responding to the aspirations of the citizen and the requirements of development and modernity, which makes all policies embody this at the level of public utilities, using modern technology represented in electronic management, which is related to the development of the National Observatory The public utility and its development at all internal and external levels to serve the public interests.
مذكرة ماستر
Keywords: المرفؽ العا، المصمحة العامة، التطور، الحداثة.; public utility, public interest, development, modernity.